Multi-Sensor Internet of Things System for Monitoring Wastewater in Healthcare Facility - Purnama, Sevia Indah; Afandi, Mas Aly; Hikmah, Irmayatul (Jurnal Rekayasa Elektrika, 2025)
Wastewater produced by healthcare facilities must meet the parameter criteria set by the Ministry of Environment and Forestry. These criteria ensure that the discharged wastewater does not harm the environment. The numerous healthcare facilities in an area and irregular monitoring can lead to inaccuracies in recording wastewater content. Technology that can be used for periodic monitoring of wastewater content in healthcare facilities is multi-sensor technology and the internet of things (IoT). This paper aims to develop the devices utilizing multi-sensor technology and IoT for monitoring wastewater parameter criteria in healthcare facilities. The developed device measures pH, turbidity, oxidation reduction potential (ORP), and temperature parameters in the wastewater. The sensor data test results showed an accuracy of 98.77% with a precision of 10.03 0.13 for the pH parameter. The ORP parameter showed an average accuracy of 97.56% with a precision range of 241.20 5.65. The turbidity parameter showed an average accuracy of 96.20% with a precision range of 101,67 3,11. The temperature parameter showed an average accuracy of 97.80% with a precision range of 39.23 0.73. Data transmission to the platform had an average delay of 88.02 ms with an average jitter 0.23 ms. Based on the performance measurement data for sensor and data transmission categories, the proposed device met the research aim in monitoring wastewater conditions in healthcare facilities. The device improve the documentation process in monitoring watewater parameter in healthcare facility. The monitoring results using the device showed that the three healthcare facilities met the criteria required by Indonesian Ministry of Environment and Forestry.